Hypoperfusion assessed by pressure reactivity index is associated with delayed cerebral ischemia after subarachnoid hemorrhage: an observational study - Bin Bin Fan; Xiao Chuan Sun; Zhi Jian Huang; Xiao Min Yang; Zong Duo Guo; Zhao Hui He (Chinese Neurosurgical Journal, 2021)
Abstract Background Dysfunction of cerebral autoregulation is one of the pathophysiological mechanisms that causes delayed cerebral ischemia (DCI) after subarachnoid hemorrhage (SAH). Pressure reactivity index (PRx) have been confirmed to reflect the level of cerebral autoregulation and used to derive optimal cerebral perfusion pressure (CPPopt). The goal of this study is to explore the associations between autoregulation, CPPopt, PRx, and DCI. Methods Continuous intracranial pressure (ICP), arterial blood pressure (ABP), and cerebral perfusion pressure (CPP) signals acquired from 61 aSAH patients were retrospectively analyzed. PRx was calculated and collected by Pneumatic computer system. The CPP at the lowest PRx was determined as the CPPopt. The duration of a hypoperfusion event (dHP) was defined as the cumulative time that the PRx was > 0.3 and the CPP was <CPPopt. The duration of CPP more than 10 mmHg below CPPopt (ΔCPPopt < − 10 mmHg) was also used to assess hypoperfusion. The percent of the time of hypoperfusion by dHP and ΔCPPopt < − 10 mmHg (%dHP and %ΔCPPopt) were compared between DCI group and control group, utilizing univariate and multivariable logistic regression. It was the clinical prognosis at 3 months after hemorrhage that was assessed with the modified Rankin Scale, and logistic regression and ROC analysis were used for predictive power for unfavorable outcomes (mRs 3–5). Results Data from 52 patients were included in the final analysis of 61 patients. The mean %dHP in DCI was 29.23% and 10.66% in control. The mean %ΔCPPopt < − 10 mmHg was 22.28%, and 5.90% in control. The %dHP (p < 0.001) and the %ΔCPPopt < − 10mmHg (p < 0.001) was significantly longer in the DCI group. In multivariate logistic regression model, %ΔCPPopt <− 10 mmHg (p < 0.001) and %dHP (p < 0.001) were independent risk factor for predicting DCI, and %ΔCPPopt <− 10 mmHg (p = 0.010) and %dHP (p = 0.026) were independent risk factor for predicting unfavorable outcomes. Conclusions The increase of duration of hypoperfusion events and duration of CPP below CPPopt over 10 mmHg, evaluated as time of lowered CPP, is highly indicative of DCI and unfavorable outcomes.